1992
DOI: 10.1128/jb.174.6.2047-2051.1992
|View full text |Cite
|
Sign up to set email alerts
|

LcrF is the temperature-regulated activator of the yadA gene of Yersinia enterocolitica and Yersinia pseudotuberculosis

Abstract: The virulence plasmid of human pathogenic Yersinia species, pYV, encodes secreted proteins, Yop proteins, and an outer membrane protein, YadA. YadA has been associated with binding to a variety of substrates and with interference with host defense. YadA is regulated by temperature and is expressed only at 37 degrees C. Unlike the yop regulon, the yadA gene is not under Ca2+ regulation. Here, we show that LcrF (VirF), the temperature-regulated activator of the yop regulon, also acts as an activator for yadA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 29 publications
1
63
0
1
Order By: Relevance
“…Deleting any single component of the TTSS attenuates bacterial virulence, suggesting that the Yops, Sycs, and other accessory proteins assemble into a large multisubunit complex. As an essential component of the coordinately regulated low Ca 2ϩ response stimulon (LCR) of pCD1, LcrF stimulates maximum expression of LcrV and Yops at 37°C, and this activation step requires host cell contact or Ca 2ϩ depletion (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Deleting any single component of the TTSS attenuates bacterial virulence, suggesting that the Yops, Sycs, and other accessory proteins assemble into a large multisubunit complex. As an essential component of the coordinately regulated low Ca 2ϩ response stimulon (LCR) of pCD1, LcrF stimulates maximum expression of LcrV and Yops at 37°C, and this activation step requires host cell contact or Ca 2ϩ depletion (16,17).…”
mentioning
confidence: 99%
“…Deleting any single component of the TTSS attenuates bacterial virulence, suggesting that the Yops, Sycs, and other accessory proteins assemble into a large multisubunit complex. As an essential component of the coordinately regulated low Ca 2ϩ response stimulon (LCR) of pCD1, LcrF stimulates maximum expression of LcrV and Yops at 37°C, and this activation step requires host cell contact or Ca 2ϩ depletion (16,17).As an approach to study the assembly of the Y. pestis virulence machinery, we used a two-step screening process to identify direct interactions between pairs of TTSS proteins. Protein interactions were first detected by surface plasmon resonance (SPR) and then classified according to the strength of interaction at equilibrium.…”
mentioning
confidence: 99%
“…This strongly suggests that YadA and invasin of YeO:3 act cooperatively, whereby YadA promotes efficient cell attachment allowing invasin to initiate the entry process (figure 1). These properties seem to be YeO:3 specific, as previous studies with YeO:8 and Y. pseudotuberculosis showed that invasin and YadA are differentially expressed and constitute independent colonization factors that are active at separate sites and/or during different stages of the infection (Eitel & Dersch, 2002;Pepe et al, 1994;Skurnik & Toivanen, 1992).…”
Section: Efficient Host Cell Adhesion and Invasion Of Yeo:3 Is Mediatmentioning
confidence: 71%
“…Another important adhesion factor is YadA which is only expressed at 37°C (El Tahir & Skurnik, 2001;Skurnik & Toivanen, 1992). YadA belongs to the family of trimeric autotransporter adhesins and was shown to bind with high affinity to collagen and laminin (Leo et al, 2008;Skurnik & Toivanen, 1992). To investigate the colonization mechanisms of YeO:3 strains, we compared their cell adhesion and invasion properties with that of other Y. enterocolitica serotypes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation